Can hospital accreditation enhance patient experience? Longitudinal evidence from a Hong Kong hospital patient experience survey - Ellie Bostwick Andres; Wen Song; Wei Song; Janice Mary Johnston (BMC, 2019)
Abstract Background Hospital accreditation is expected to improve health care quality and patient satisfaction. However, little and conflicting evidence is currently available to support its effect on patient outcomes, particularly patient experience. Hong Kong recently launched a pilot programme to test an infrastructure for accreditation of both private and public hospitals with the Australian Council on Healthcare Standards. This study aims to evaluate the longitudinal impact of hospital accreditation on patient experience in a publicly-funded university teaching hospital in Hong Kong. Methods Three cross-sectional surveys were conducted at three time points: 9 months pre- accreditation as baseline (T1), three (T2) and fifteen months (T3) post-accreditation. Acute care inpatients aged 18 to 80 were recruited on the second day of hospital admission to complete the Picker Patient Experience Questionnaire-15 (PPE-15). Baseline data was first compared to the 2005 Hong Kong average for public hospitals using t-tests. Data was then analyzed using ANOVA and multiple linear regression to evaluate differences across the three cross-sections and examine the effect of accreditation over time while controlling for covariates. Results 3083 patients (T1 = 896, T2 = 1093, T3 = 1094) completed the survey for a response rate of 83.5, 86.1, and 83.8%, respectively. The hospital baseline domain and summary patient experience scores differed from the Hong Kong public hospital average obtained from the 2005 Thematic Household Survey. All domain and summary patient experience scores declined (improved) over the study period (T1 to T3). The multiple regression results confirmed the time point score comparisons with declining (improving) parameter estimates for T2 and T3 for all domain and summary scores except the 'continuity and transition' domain, for which the declining coefficient was only significant at T3. Conclusions While hospital accreditation has not been shown to improve patient outcomes, this study suggests the accreditation exercise may enhance patient experience. Moreover, it suggests the quality improvement initiatives associated with accreditation may address areas of concern emphasized by Hong Kong patients, such as involvement in care and emotional support from providers.